2021
DOI: 10.21203/rs.3.rs-145240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Permanent Stoma: A Quality Outcome in Treatment of Rectal Cancer and Its Impact on Length of Stay

Abstract: Background This study aimed to identify socioeconomic predictors of permanent stoma in rectal cancer treatment and examine its association with length of stay at the treatment facility.MethodsRectal cancer patients were identified from the Agency for Health Care Administration Florida Hospital Inpatient Discharge Dataset. Multivariate regression models were utilized to identify demographic, and socioeconomic factors associated with receiving a permanent stoma as well as the associated length of stay of these … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This is important because the decision regarding which operation to perform considers several different factors including the location (height from anal verge) and staging of the tumor, comorbidities, likely functional outcome, response to neoadjuvant therapy, patient preference, and surgical experience/skill. The wider literature has demonstrated that disparities in stoma formation may also reflect socio‐demographic and geographic differences across populations 25 …”
Section: Methodsmentioning
confidence: 99%
“…This is important because the decision regarding which operation to perform considers several different factors including the location (height from anal verge) and staging of the tumor, comorbidities, likely functional outcome, response to neoadjuvant therapy, patient preference, and surgical experience/skill. The wider literature has demonstrated that disparities in stoma formation may also reflect socio‐demographic and geographic differences across populations 25 …”
Section: Methodsmentioning
confidence: 99%